Analysis of Critical Factor for BOT Highway Project - Mrs. Wable Arti; Asst. Prof. Prashant Suryavanshee; Dr. Kamal Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In our country, generally it is difficult for government or any public organization to arrange fund for any development activity, so this BOT type project are very useful. Now lots of project in India are taken in this scheme in various sectors like Highway, Bridge, Irrigation, Airport etc. Now the problem arises mainly to check whether a project is viable in this scheme or not. In this study we tried to find out main governing factor for a BOT project. In this study the critical factors will analyze and identify the hierarchy of these factors and their inter-relationship. This study can be used as reference before finalizing factors and their relationship for any BOT Highway project. This study can be used to check viability for any BOT project. For the successful implementation of Build- Operate and Transfer Project, careful evaluations of different parameters are must.